Global Supply Chain Operations for Investment Locations Selection in Climate Change Variation - Anita Sitawati; Herika Taki; Hanny W Wiranegara; Yayat Supriatna; Rezkia Dewi Andajani (School of Postgraduate Studies, Diponegoro Univer, 2024)
A livable city is a city where people can live comfortably and peacefully. The success of a livable city is achieved not only by physical advantage factors but also by social and economic factors. Livable cities must be investment-friendly to support economic functions. Investment-friendly cities will be the preferred locations for multinational corporations. Urban planners, designers, and managers need to devise urban development strategies that attract investors. This research aims to identify pivotal factors that drive investors' decision-making in selecting investment locations. This study focuses on the influence of global supply chain operations on investment location selection in the era of climate change, which is still relatively rare as it attempts to formulate regional development policies based on a demand-side approach. A demand-based approach requires identifying the investor's point of view in the investment location selection process. The Electronics and Automotive industry in the JABABEKA Industrial Area, Jakarta, Indonesia, is used as a case study. Primary data was collected from the respondents' perceptions and analyzed using the Structural Equation Model (SEM) method, applied in the software Smart PLS 3.2.8. The structural model used in this approach is formative. On a global scale, the choice of Indonesia as an investment location is influenced by (i) aspects of physical, social, and economic advantages related to cross-border trade and (ii) aspects of the supply chain related to the impact of climate change.